The Effect of Bottom Rocker Sole on Kinetic Energy in Transtibial Prosthesis Users - Nugroho, Agus Setyo; Suprayogi, Dody (Poltekkes Kemenkes Jakarta I, 2022)
Background : Lower limb amputation with or without the use of a prosthesis has an impact on energy consumption/needs for ambulances. There are studies that say the results of the measurement of energy used in amputated patients, namely walking with a partially amputated leg will expend more energy than the amputee. Higher than the study, it can be said that more energy expenditure results in fatigue one level above the fatigue that is experienced felt in normal people. The purpose of this study was to determine the effect of the bottom rocker sole on the kinetic energy of transtibial prosthesis users. Methods: This type of research is quasi-experimental with a pre and post test design approach. This research was conducted at APOC Clinic in April - July 2021, with the research subjects being 20 users of the transtibial prosthesis. Each research subject will be given an intervention in the form of a bottom rocker sole, then measured for kinetic energy before and after treatment. Analysis of the data in this study using the Wilcoxon test. Results: There is a statistically significant effect of the use of the buttom rocker sole on the kinetic energy of the transtibial prosthesis users (z = -2.73, mean difference 1.5 and p value = 0.006). Conclusion: The use of buttom rocker sole can increase the occurrence of kinetic energy in transtibial prosthesis users so that they can maximize their activities.